The variations of wheat–maize production, soil organic carbon, and carbon footprints: insights from a 20–year on–farm observational experiment in the North China Plain - Wang, Ning; Ai, Zhipin; Zhang, Qiuying; Leng, Peifang; Qiao, Yunfeng; Li, Zhao; Tian, Chao; Shi, Xinjie; Cheng, Hefa; Chen, Gang; Li, Fadong (Frontiers in Plant Science, 2025)
IntroductionClimate change is a substantial threat to the global food supply, especially for the North China Plain (NCP), a critical agricultural region in China that exhibits high sensitivity and vulnerability to climate change. Under climate change, many uncertainties remain regarding crop yields, soil organic carbon (SOC), and greenhouse gas (GHG) emissions.MethodsA 20−year on−farm observational study (2003−2022) of a winter wheat−summer maize rotation system was conducted to comprehensively quantify the continuous variations in crop productivity, SOC storage, GHG emissions, and carbon footprints (CFs) in the NCP.ResultsA warming trend of 0.08°C per year and an annual increase of 57 hours in sunshine duration were detected over the study period. Both wheat and maize yields showed sustained improvements, with annual rates of 70 kg ha–1 and 184 kg ha–1, respectively. Wheat yields were primarily influenced by cumulative sunshine hours in November and soil total potassium (K) content, whereas maize yields were significantly affected by wheat-season agricultural inputs (water, N, P, K fertilizers) and initial soil properties (pH, N, P, K). Although wheat production generated higher GHG emissions than maize (7,307.5 vs 2,998.7 kg CO2-eq ha−1), the wheat season transitioned into a net carbon sink (CF < 0) due to SOC accumulation (0.58 g kg−1 year−1). Conversely, SOC depletion (-0.72 g kg−1 year−1) during the maize season resulted in a carbon source status (CF > 0). This divergence likely stems from contrasting straw management practices: wheat straw incorporation at 20 cm depth versus maize straw surface mulching.DiscussionOur findings demonstrate significant improvements in crop yields, SOC sequestration, and net ecosystem economic budget over two decades. However, the decelerating trends in yield gains and SOC accumulation rates warrant strategic attention to sustain long-term agricultural resilience.